Agromyces chromiiresistens sp. nov., Novosphingobium album sp. nov., Sphingobium arseniciresistens sp. nov., Sphingomonas pollutisoli sp. nov., and Salinibacterium metalliresistens sp. nov.: five new members of Microbacteriaceae and Sphingomonadaceae from polluted soil - Liu, Ze-Shen; Wang, Ke-Huan; Cai, Man; Yang, Mei-Ling; Wang, Xiao-Kang; Ma, Hong-Lin; Yuan, Yi-Han; Wu, Lin-Huan; Li, De-Feng; Liu, Shuang-Jiang (Frontiers in Microbiology, 2023)
Five strains were isolated and cultivated from polycyclic aromatic hydrocarbons and heavy metals polluted soil of an abandoned coking plant. Phylogenetical analysis showed that they belonged to the phyla Proteobacteria and Actinobacteria, and their 16S rRNA gene sequence identities were lower than 98.5% to any known and validly nominated bacterial species, suggesting they were potentially representing new species. Using polyphasic taxonomic methods, the 5 strains were classified as new species of the families Microbacteriaceae and Sphingomonadaceae. The proposed names of the 5 novel species are Agromyces chromiiresistens (type strain H3Y2-19a T =CGMCC 1.61332 T ), Salinibacterium metalliresistens (type strain H3M29-4 T =CGMCC 1.61335 T ), Novosphingobium album (type strain H3SJ31-1 T =CGMCC 1.61329 T ), Sphingomonas pollutisoli (type strain H39-1-10 T =CGMCC 1.61325 T ), and Sphingobium arseniciresistens (type strain H39-3-25 T =CGMCC 1.61326 T ). A. chromiiresistens H3Y2-19a T and Sphingobium arseniciresistens H39-3-25 T were robustly resistant to chromate (VI) and/or arsenite (III). Sphingomonas pollutisoli H39-1-10 T grew on aromatic compounds including naphthalene as carbon sources even in the presence of chromate (VI) and arsenite (III). These features reflected their adaptation to the polluted soil environment.